Organelle Redox of CF and CFTR-Corrected Airway Epithelia - Schwarzer, Christian (2007)
In cystic fibrosis reduced CFTR function may alter redox properties of airway epithelial cells. Redox-sensitive GFP (roGFP1) and imaging microscopy were used to measure redox potentials of cytosol, ER, mitochondria and cell surface of cystic fibrosis nasal epithelial cells and CFTR-corrected cells. We also measured glutathione and cysteine thiol redox states in cell lysates and apical fluids to provide coverage over a range of redox potentials and environments that might be affected by CFTR. As measured with roGFP1, redox potentials at the cell surface (~ -207 ±8 mV) and in the ER (~ -217 ±1 mV) and rates of regulation of the apical fluid and ER lumen following DTT treatment were similar for CF and CFTR-corrected cells. CF and CFTR-corrected cells had similar redox potentials in mitochondria (-344 ±9 mV) and cytosol (-322 ±7 mV). Oxidation of carboxy-dichlorodihydrofluoresceindiacetate and of apical Amplex Red occurred at equal rates in CF and CFTR-corrected cells. Glutathione and cysteine redox couples in cell lysates and apical fluid were equal in CF and CFTR-corrected cells. These quantitative estimates of organelle redox potentials combined with apical and cell measurements using small molecule couples confirmed there were no differences in redox properties of CF and CFTR-corrected cells.